United Kingdom’s Market Investigation Powers Under the Enterprise Act 2002 in the Context of EU’s New Competition Tool Proposal - Mleczko, Marcin (Teisė, 2023)
In this article, the author is aiming to look at the United Kingdom’s system of market investigations, which involves quite extensive procedural safeguards, and is trying to see whether there are any lessons which could be learned and later used in developing the New Competition Tool or a similar market investigation tool on the European Union level.